2018
DOI: 10.3389/fpsyt.2018.00675
|View full text |Cite
|
Sign up to set email alerts
|

Low Field Magnetic Stimulation Ameliorates Schizophrenia-Like Behavior and Up-Regulates Neuregulin-1 Expression in a Mouse Model of Cuprizone-Induced Demyelination

Abstract: White matter and myelin sheath integrity are disrupted in schizophrenia, and non-invasive magnetic brain stimulation targeting these tracts is a promising new therapeutic approach. In particular, deep-brain reachable low field magnetic stimulation (DMS) could alleviate cognitive impairment and depressive-like behaviors in animal models. In this study, we sought to assess the effects of DMS on myelin sheath damage and schizophrenia-like behaviors in the cuprizone-induced demyelination mouse model. Mice were fed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 58 publications
(64 reference statements)
3
13
0
Order By: Relevance
“…Consuming a CPZ-containing diet for 5 weeks impaired the social recognition and spatial working memory of mice, which are consistent with the findings in previous studies (Xiao et al, 2008;Xu et al, 2009Xu et al, , 2010Sun et al, 2018;Zhang J. et al, 2018). Moreover, the present study showed that rTMS completely blocked the CPZ-induced deficits in spatial memory and social recognition of mice, but the sham stimulation did not show this protective effect.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Consuming a CPZ-containing diet for 5 weeks impaired the social recognition and spatial working memory of mice, which are consistent with the findings in previous studies (Xiao et al, 2008;Xu et al, 2009Xu et al, , 2010Sun et al, 2018;Zhang J. et al, 2018). Moreover, the present study showed that rTMS completely blocked the CPZ-induced deficits in spatial memory and social recognition of mice, but the sham stimulation did not show this protective effect.…”
Section: Discussionsupporting
confidence: 92%
“…Feeding C57BL/6 mice with a 0.2% CPZ-supplemented diet for 4-6 weeks was shown to induce acute demyelinating lesions followed by spontaneous remyelination in the brains of subjects (Hiremath et al, 1998;Matsushima and Morell, 2001). In addition to demyelination and loss of mature oligodendrocytes (OLs, the myelin-forming cells in the brain), CPZ-exposed mice also showed astrocyte proliferation and microglia activation in the lesion sites of the brain (Stidworthy et al, 2003;Remington et al, 2007;. These neuropathological features constitute the constructive validity of CPZ-exposed mice being used as an animal model of multiple sclerosis (MS), a major demyelinating disease of the central nervous system.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several independent studies have identified that neurotrophin 1 (NRG-1) and its receptor epidermal growth factor 4 (ErbB4) are important susceptibility genes for schizophrenia, however, their exact role in the pathogenesis of schizophrenia remains unknown [7][8][9]. Studies have shown that NRG-1 and ErbB4 signalling pathways regulate the expansion of inhibitory electrical activity in the mammalian cerebral cortex by autonomously regulating the connectivity of specific gamma-aminobutyric acid (GABA) interneurons [10]. Other studies have suggested different theories for this.…”
Section: Introductionmentioning
confidence: 99%